3-방향 직물 복합재료 모델링 및 붐 구조물의 거동 연구 - 변선우(Seon-Woo Byun); 양지윤(Ji-Yoon Yang); 이수용(Soo-Yong Lee); 노진호(Jin-Ho Roh) (항공우주시스템공학회지, 2022)
This paper studied the mechanical characteristics of boom structures by verifying the modeling method of representing unit cells of triaxial woven fabric (TWF) composites. The modeling of the representative unit cell obtained the ABD matrix by analysing the behaviour of tensile, shear, bending, and torsion using the periodic boundary conditions for the beam element. This study aimed to validate the ABD matrix by comparing the tensile analysis output from a finite element program with the experimental results from an MTS 810 machine. Additionally, the mechanical characteristics of a TWF composite boom structure were determined through bending analysis and experiments. The findings of this research are expected to be beneficial for developing structures using TWF composites. 본 논문은 3-방향 직물 복합재료의 대표 단위 셀의 모델링 방법에 대해 검증하여 붐 구조물의 기계적 특성에 대해 연구하였다. 대표 단위 셀의 모델링에는 빔 요소에 주기적 경계 조건을 이용하여 인장, 전단, 굽힘, 비틀림의 거동을 모사한 해석을 통해 ABD 행렬을 구했다. 유한 요소 프로그램을 통한 인장 해석과 만능재료 시험기를 이용한 실험 결과를 비교하여 ABD 행렬을 검증하였다. 3-방향 직물 복합재료 붐 구조물의 기계적 특성을 굽힘 해석과 실험을 통해 확인하였다. 이를 통해 3-방향 직물 복합재료를 이용한 구조물 거동 특성을 확인하고자 한다.